Oxidation resistance improvement of ZrB2 powders by the deposition of Al2O3/Y2O3/ZrO2 coatings via chemical coprecipitation method. (January 2019) - Feng, X Q; Wang, X; Liu, Y; Guo, Y; Zhang, M; Zhang, L; Xie, J L; Deng, L J
Abstract: Zirconium diboride (ZrB2 ) is an important class of advanced ceramic material with excellent performance and good application prospect, but the oxidation restricts its application greatly. In order to improve the oxidation resistance of ZrB2 ceramics at high temperature, we coat Al2 O3, Y2 O3 and ZrO2 layers on the surface of ZrB2 particles to prepare the ZrB2 @Al2 O3, ZrB2 @Y2 O3 and ZrB2 @ZrO2 composite particles via the chemical co-precipitation method. The results of XRD SEM and EDS strongly suggest that the coated composite particles are prepared successfully, while TG and DSC curves prove that the oxidation resistance of ZrB2 particles can be improved significantly by the proposed method.